Abiotic reduction of uranium(VI) with humic acid at mineral surfaces: Competing mechanisms, ligand and substituent effects, and electronic structure and vibrational properties. (November 2019) - Wang, Qian; Zhu, Chang; Huang, Xiaoxiao; Yang, Gang
Abstract: Abiotic reduction represents an attractive technology to control U(VI) contamination. In this work, an abiotic route of U(VI) reduction with humic acid at mineral surfaces is proposed and reaction mechanisms are addressed by periodic density functional theory calculations. Different influencing factors such as ligand effect, content of CO3 2− ligands and substituent effect are inspected. The coordination chemistry of uranyl(VI) surface complexes relies strongly on substrates and ligands, and the calculated results are in good agreements with experimental observations available. For the OH − ligand, two competitive mechanisms co-exist that respectively produce the U(IV) and U(V) species, and the former is significantly preferred because of lower energy barriers. Instead, the NO3 − ligand leads to the formation of U(V) while for the Cl − ligand, the U(VI) surface complex remains very stable and is not likely to be reduced because of very high energy barriers. The U(V) and U(IV) complexes are the predominant products for low and high CO3 2− contents, respectively. Accordingly, the abiotic reduction processes with humic acid are efficient to manage U(VI) contamination and become preferred under basic conditions or at higher CO3 2− contents. The U(VI) reduction is further promoted by introduction of electron-donating rather than electron-withdrawing substituents to humic acid. Electronic structure analyses and vibrational frequency assignments are calculated for the various uranium surface complexes of the reduction processes, serving as a guide for future experimental and engineered studies. The molecular-level understanding given in this work offers an abiotic route for efficient reduction of U(VI) and remediation of U(VI)-contaminated sites at ambient conditions. Graphical abstract: Image 1 Highlights: An abiotic route of U(VI) reduction with humic acid at mineral surfaces is posed. Competing mechanisms and abundant molecular-level information are presented. Degree of U(VI) reduction can be efficiently regulated by choice of anionic ligands. Control of U(VI) pollution is preferred at basic conditions or high CO3 2− contents. U(VI) reduction is promoted by adding electron-donating substituents to humic acid.